ISOL Examining cultural representation in Kurikulum Merdeka English textbooks: A content analysis - Syntha Octoviani; Deisyi Anna Batunan; Fridolin Kukus (Universitas Muhammadiyah Purwokerto, 2026)
Framed from a qualitative content analysis, this study aims to examine cultural representations and the promotion of intercultural communicative competence within three Kurikulum Merdeka textbooks: Work in Progress (Grade 10), English for Change (Grade 11), and Life Today (Grade 12). The findings indicate that cultural products are more prominently represented than persons, perspectives, and practices. In terms of Kachru’s three circles, expanding circle cultures—primarily Indonesian cultures—are overwhelmingly represented, whereas inner circle and outer circle cultures receive comparatively limited attention. Regarding ICC dimensions, the textbooks show stronger emphasis on the development of knowledge than attitudes and critical cultural awareness. Moreover, the skills of interpreting/relating and discovery/interaction are insufficiently addressed. The study recommends a more balanced representation of cultural aspects across the three circles, along with a more systematic integration of intercultural communicative competence. This study provides empirical evidence of the gap between the goals of the Kurikulum Merdeka and the implementation of the curriculum in the textbooks. It provides practical guidance for textbook developers, curriculum designers, and educators to create more balanced materials that systematically integrate ICC, especially the interpreting/relating and discovery/interaction dimensions, which are still underdeveloped, enabling Indonesian students to develop both cultural roots and global intercultural competencies.